BUSINESS MODEL DEVELOPMENT DESIGN FOR TWA PANGANDARAN AS A SUSTAINABLE ECOTOURISM DESTINATION - Setiawati, Caroline
Taman Wisata Alam Pangandaran is a legendary ecotourism destination in Pangandaran. The large public interest in nature tourism after the Covid-19 pandemic has become an opportunity for the return of the nature-based tourism sector. However, Taman Wisata Alam Pangandaran has actually experienced a decline in tourists due to the rise of artificial nature tourism. The potential natural beauty of Taman Wisata Alam Pangandaran can be utilized as an attraction for tourists. Ecotourism-based tourism development is actually inseparable from the principles of conservation, education, tourism, economy, and community participation. Therefore, sustainable development is needed by taking into account the carrying capacity of natural tourism areas. This study aims to calculate the carrying capacity of Taman Wisata Alam Pangandaran using the Cifuentes (1992) method, capacity, and queuing models that are in accordance with the carrying capacity of tourism. The calculation results show that Taman Wisata Alam Pangandaran has a Physical Carrying Capacity of 15,053 tourists/day; Real Carrying Capacity of 1,007 tourists/day; Management Capacity of 100% and Effective Carrying Capacity of 1,007 tourists/day. Meanwhile, the demographic carrying capacity of the area is surplus with a value of 0.23. The Taman Wisata Alam Pangandaran visitor queue model with an ECC of 1,007 tourists/day has a maximum visit length of 60 minutes. This calculation is expected to be a consideration for the development of the Taman Wisata Alam Pangandaran tourist area.